MOF-templated synthesis of photoluminescent MoS2 QDs. Issue 90 (26th October 2022) - Xu, Li; Fu, Wei; Bao, Lei; Wang, Guanglin; Wang, Wanping; Wang, Wei; Xiang, Kun; Deng, Nengmei; Fu, Xucheng; Jin, Juncheng
Abstract : MOF-templated synthesis of photoluminescent MoS2 QDs. Abstract : Fabricating MoS2 QDs using porous metal–organic frameworks (MOFs) as templates remains a great challenge, because the MOF structure is prone to collapse during solvothermal reactions, resulting in a loss of the function of the template. In the present work, the production of homogeneous photoluminescent MoS2 QDs was achieved by using the structurally stable MOF MIL-101 as limited nanoreactors. The process developed opens up a new route for fabricating other photoluminescent QDs and their derived nanomaterials.